Engaging with partners in the Global South in uncertain times - Stephan Klingebiel (German Institute of Development and Sustainability (IDOS), 2022)
Having already been growing in importance for a number of years, geopolitics as it relates to the Global South has become tremendously more relevant following Russia's aggression in Ukraine in 2022. Rivalries with China are set to become even more influential in future, determining intergovernmental relations as a whole. Following the Russian invasion in February 2022, attention was initially concentrated on the stances adopted by states regarding the corresponding UN resolutions and UN debates. This focus alone illustrates the great significance attached to the positions taken by states and thus to strategic partisan thinking. At the same time, it would seem that none of the country alliances being formed to date differ fundamentally from those of recent years. Many developing countries are capitalising on their emancipated status gained in recent decades to formulate positions of their own, as well as to identify any double standards on the part of Western governments. It is important that German, European and other political players gain a better idea of the interests and perceptions of partners in the Global South. In development terms, Russia's war of aggression represents a watershed moment. It is important to note the following in this context: * At overall level, it will most likely be more difficult to achieve the 2030 Agenda, with its 17 SDGs (Sustainable Development Goals). The COVID-19 pandemic had already produced a huge socio-economic shock in the Global South, but this has now been dwarfed in many developing countries by the impact of the war. On top of this, the increasingly critical effects of climate change are proliferating all the time. * While the most severe consequences of the Ukraine war are being felt by the country itself (need for comprehensive humanitarian assistance; future need for large-scale reconstruction work) and the surrounding region (refugee care, etc.), the surge in food and energy prices resulting from the conflict is having a major impact on developing countries. * There are also other long-term challenges in regard to global sustainable development. Take innovative cooperation instruments for tackling climate change, for instance, the most prominent of which are just energy transition partnerships (JETP). The legitimacy of efforts to promote these ambitious cooperation initiatives could be undermined by European countries introducing short-term measures that involve a return to fossil fuel investment. * The growing need to overcome cross-border challenges could intersect with cutbacks being made by donor countries to their long-term development programmes. For example, some nations (particularly the UK and, in some cases, Germany) may scale back funding or increasingly charge for providing in-donor refugee costs and thus move to report a number of their activities as Official Development Assistance (ODA) (as planned by the Netherlands and Norway, for instance). * We can expect the Ukraine war to reinforce the general trend towards interest-based development policy and increase demand for approaches that deliver quick results. Nevertheless, it is not possible to derive a clear regional, thematic or country allocation pattern from this trend. * The issue of governance in developing countries is receiving greater attention in light of the risks posed by autocratic systems. The increase in cooperation with China and Russia, two nations employing their own global discourse in an attempt to promote what they refer to as 'real democracy', is especially indicative of the way China in particular is striving to influence global debate.
Keywords: 320; Development policy; Global South; West; Russia; Pandemic; Africa; China